Economic evaluation of human urinary kallindinogenase for patients with acute ischemic stroke in China. (3rd August 2018) - Lin, Ziyi; Rao, Xiuqin; Zhang, Zhijun; Xuan, Jianwei
Abstract: Objectives: In China, both human urinary kallindinogenase (HUK) and 3-n-butylphthalide (NBP) are recommended for clinical use to improve cerebral blood circulation during an acute ischemic stroke (AIS). The objective was to evaluate the economic value of HUK vs NBP for patients with AIS from a Chinese payer's perspective. Methods: An economic evaluation based on data of patients who have been treated with either HUK ( n = 488) or NBP ( n = 885) from a prospective, phase IV, multi-center, clinical registry study (Chinese Acute Ischemic Stroke Treatment Outcome Registry, CASTOR) was conducted to analyze the cost and effectiveness of HUK vs NBP for AIS in China. Before the analysis, the patients were matched using propensity score. Both a cost-minimization analysis and a cost-effectiveness analysis were conducted to compare the matched pairs. A bootstrapping exercise was conducted for the matched arms to demonstrate the probability of one intervention being cost-effective over another for a given willingness-to-pay for an extra quality-adjusted life-year (QALY). Results: After propensity score matching, 463 pairs were matched. The overall medical cost in the HUK arm is USD 2, 701.20, while the NBP arm is USD 3, 436.83, indicating HUK is preferred with cost-minimization analysis. Although the QALY gained in the HUK arm (0.77176) compared with the NBP arm (0.76831) is statistically insignificant ( p = .4862), the cost-effectiveness analysis as exploratory analysis found that, compared with NBP, HUK is a cost-saving strategy with the lower costs of USD 735.63 and greater QALYs gained of 0.00345. Among the 5, 000 bootstrapping replications, 100% indicates that HUK is cost-effective compared with NBP under a 1-time-GDP threshold; and 97.12% indicates the same under a 3-time-GDP threshold. Conclusion: This economic evaluation study indicates that administrating HUK is a cost-saving therapy compared with NBP for managing blood flow during AIS in the Chinese setting.